Trends in user ratings and reviews of a popular yet inaccurate blood pressure-measuring smartphone app. (7th June 2018) - Plante, Timothy B; O'Kelly, Anna C; Macfarlane, Zane T; Urrea, Bruno; Appel, Lawrence J; Miller III, Edgar R; Blumenthal, Roger S; Martin, Seth S
Abstract: Objective: To understand whether user reviews of Instant Blood Pressure (IBP), an inaccurate, unregulated BP-measuring app reflected IBP's inaccuracy, to understand drivers for high and low ratings, and to understand if disclaimers prevented medical use. Materials and Methods: All iTunes app reviews for IBP v1.2.3 were downloaded and assessed for themes by two reviewers. Summary statistics for themes were tabulated with their associated star ratings. Results: Common themes included perceived accuracy (42% of all reviews, star rating mean 4.8, median 5), inaccuracy (10%, 2.0, 1), and convenience (34%, 4.7, 5). Nine percent documented IBP use in medical conditions (4.6, 5), and 2% mentioned IBP's disclaimer (2.7, 3). Discussion: User reviews and ratings of a popular, inaccurate BP-measuring app were positive and uncommonly commented on its inaccuracy. Disclaimers attempting to prevent medical use of the app were ineffective. These findings support the need for more rigorous regulatory review of apps prior to their release.